Strategies to Develop Cemagi as a Community Based-Tourism Village and to achieve the status as an Independent Tourism Village in Bali - Ningsih, Gusti Ayu Putu Bella Harta; Suasapha, Anom Hery; Aridayanti, Dewa Ayu Nyoman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to design strategies for developing Cemagi Tourism Village as a community-based and Independent Tourism Village. A qualitative and descriptive approach was used in this research. The primary data was collected through interviews with informants who were chosen purposively. Observation and documentation were also used to collect the primary and secondary data. The results found 13 indicators of strengths, 10 of weaknesses, 6 of opportunities, and 3 threats for Cemagi Village to be recognized as an Independent Tourism Village based on Community-Based Tourism Concepts. The analysis also recommends implementing the SO Strategies that Cemagi Tourism Village can carry out as an independent community-based tourism village. The strategies are: 1). Optimizing potential development as a community-based tourist attraction, 2). Creating combined tour packages, 3). Providing daily performances, 4). Asking for government assistance, 5). Increasing the availability of homestays, 6). Providing cultural festivals, 7). Empowering the local community, 8). Increasing promotion, 9). Creating tour packages, 10). Designing a masterplan, and 11). Designing collaborative content for marketing purposes.